Analysis of Debris Flow Reduction Effect of Check Dam Types considering the Mountain Stream Shape: A Case Study of 2016 Debris Flow Hazard in Ulleung-do Island, South Korea - Man-Il Kim; Namgyun Kim (Advances in Civil Engineering)
Ulleung-do is a volcanic island located 130 km east of the Gangwon-do province of South Korea. It is characterized by steep slopes covered with effusive rocks released from multiple volcanic activities. Having accumulated deep colluvium, Ulleung-do Island manifests a high vulnerability to landslides frequently caused by heavy rains or typhoons, debris flow, rockfall, and other disaster hazards in mountainous areas. Therefore, facilities and residential areas located in the lower areas of the island sustain widespread damage. Hence, the installation of check dams designed to reflect the area’s local conditions is required to avoid further damage. In line with that, this study analyzes the disaster cases in Ulleung-do’s mountain areas and the effect of check dams in debris flow reduction for each type using the KANAKO-2D model. At observation point 1, the result shows that the maximum rate of debris flow is reduced by 48.5% with an open-type check dam installed and 62.9% with a closed-type check dam installed from the level without a check dam. For observation point 2, the maximum flow depth decreases by 49.7% with an open-type check dam and 77.4% with a closed-type check dam. Thus, this study suggests that the simple installation of check dams in a mountain stream that has experienced debris flow effectively mitigates damage brought by various disasters.